Worst-Case Performance Optimization Beamformer with Embedded Array's Active Pattern. (24th June 2018) - Luo, Yuyue; Pan, Jin; Zhang, J. Andrew; Huang, Shaode
Abstract : This paper proposes an adaptive array beamforming method by embedding antennas' active pattern in the worst-case performance optimization algorithm. This method can significantly reduce the beamformer's performance degradation caused by inconsistency between hypothesized ideal array models and practical ones. Simulation and measured results consistently demonstrate the robustness and effectiveness of the proposed method in dealing with array manifold mismatches.